Modeling and Simulation of MPPT-SEPIC Combined Bidirectional Control Inverse KY Converter Using ANFIS in Microgrid System - Soedibyo Soedibyo; Farid Dwi Murdianto; Suyanto Suyanto; Mochamad Ashari; Ontoseno Penangsang (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Photovoltaic system (PV) is widely used in various renewable energy application. The main problem of PV system is how to get the maximum output power which is integrated in microgrid system. Furthermore, the redundancy output power generated by on a distribution system should also be considered. This study utilizes the excess power for energy storage using bidirectional of KY inverse converter. Since the DC voltage which generated by PV and the energy storage will be converted into AC voltage using inverter toward load. This paper proposes ANFIS as search optimization method using SEPIC converter with a maximum efficiency of 99.95% to impact to power generation performance  in microgrid system.